2019
DOI: 10.1515/chem-2019-0079
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Human Serum Albumin Glycation on the Binding Affinities for Natural Flavonoids

Abstract: Increasing the degree of glycation in diabetes could affect the ability of plasma proteins in binding to small molecules and active compounds. In this study, the influence of glycation of Human serum albumin (HSA) on the binding affinities for six dietary flavonoids was investigated by fluorescence spectra. Glycated HSA was prepared through incubation with glucose and characterized by several methods to confirm the glycation. It was found that the level of glycation increased with the increasing incubation tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
3
2
0
Order By: Relevance
“…The appearance of new ICD band(s) serve(s) as clear evidence of the interaction between the host molecule and the ligand [36]: this could be observed for both conjugates. Interestingly, Liu et al revealed that glycated human serum albumin has increased binding affinity to flavonoids, such as apigenin, which could affect the metabolism of these compounds in diabetic patients [37]. This finding can support our study, i.e., the binding affinity (therefore solubility) improving properties of modified albumin to apigenin could be valuable in drug delivery.…”
Section: Discussionsupporting
confidence: 88%
“…The appearance of new ICD band(s) serve(s) as clear evidence of the interaction between the host molecule and the ligand [36]: this could be observed for both conjugates. Interestingly, Liu et al revealed that glycated human serum albumin has increased binding affinity to flavonoids, such as apigenin, which could affect the metabolism of these compounds in diabetic patients [37]. This finding can support our study, i.e., the binding affinity (therefore solubility) improving properties of modified albumin to apigenin could be valuable in drug delivery.…”
Section: Discussionsupporting
confidence: 88%
“…It can be clearly observed that intensity of fluorescence decreased with the glycation of BSA: native BSA-DRUG > g10_BSA-DRUG > g30_BSA-DRUG, indicating changes in the protein's environment induced by glucose attachment. This trend is similar to interactions of gliclazide with glycated albumin, as shown in a previous study, and remains in accordance with results obtained by other researchers, as well as for human serum albumin (HSA) [11,24,25].…”
Section: Fluorescence Quenching Of Bsa By Gliclazide In the Presence Of Cilazapril Atorvastatin And Acetylsalicylic Acidsupporting
confidence: 92%
“…Similar effects and variations, in affinity at comparable levels of glycation, have been noted in recent studies examining the binding of sulfonylureas with glycated HSA both in vitro and in vivo [9,33]. On the other hand, some researchers observed increased K a values upon glycation [25,34]. Such results were obtained for PROTEIN-ATOR-GLICL.…”
Section: Fluorescence Quenching Of Bsa By Gliclazide In the Presence Of Cilazapril Atorvastatin And Acetylsalicylic Acidsupporting
confidence: 76%
“…In both studies, glycation of HSA was followed in the presence of FAs. The other studies used a non-physiological molar ratio of HSA:glucose for glycation in the absence of FAs, and the decrease in Trp214 fluorescence was very profound [32]. HSA can be substantially modified by oxidative or carbonyl stress if the stressor concentrations are significantly higher than in the physiological conditions or in an incubation period longer than the half-life of HSA [21,22,32].…”
Section: Discussionmentioning
confidence: 99%
“…The other studies used a non-physiological molar ratio of HSA:glucose for glycation in the absence of FAs, and the decrease in Trp214 fluorescence was very profound [32]. HSA can be substantially modified by oxidative or carbonyl stress if the stressor concentrations are significantly higher than in the physiological conditions or in an incubation period longer than the half-life of HSA [21,22,32]. However, the mild modification of HSA structure was found in in vivo or in vitro studies when the concentration of stressors was in the pathophysiological range [24,27,33].…”
Section: Discussionmentioning
confidence: 99%